2017
DOI: 10.23987/sts.60523
|View full text |Cite
|
Sign up to set email alerts
|

Nearshore Wind Resistance on Denmark’s Renewable Energy Island

Abstract: The Danish island Samsø is world-famous as Denmark's Renewable Energy Island. 21 wind turbines supply the island's electricity. Today, public hostility toward a projected nearshore wind farm off the island's preserved northern coast is growing. This paper takes its main theoretical cue from Gomart and Hajer's (2003) call to open up political questions to empirical inquiry and to pay attention to the material settings in which political questions unfold. The paper seeks to make sense of the islanders' unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…Moreover, rather than focusing on a specific energy technology, our aim was to test the theoretical model on the effects of trust and influence over decisions on project acceptability. Future research could test whether similar results are found when studying more controversial renewable energy projects, such as wind power projects, or hydro-energy projects [6,8,53]. Maybe when project acceptability is generally lower, having only high trust or influence over major decisions regarding the project is not sufficient to increase project acceptability -in such cases, both may be needed for higher project acceptability.…”
Section: General Discussion and Conclusionmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, rather than focusing on a specific energy technology, our aim was to test the theoretical model on the effects of trust and influence over decisions on project acceptability. Future research could test whether similar results are found when studying more controversial renewable energy projects, such as wind power projects, or hydro-energy projects [6,8,53]. Maybe when project acceptability is generally lower, having only high trust or influence over major decisions regarding the project is not sufficient to increase project acceptability -in such cases, both may be needed for higher project acceptability.…”
Section: General Discussion and Conclusionmentioning
confidence: 78%
“…Interestingly, acceptability was even higher when people had influence over major decisions, irrespective of the level of trust that people had in the responsible energy company in China. 8…”
Section: Effects Of Trust and Influence Over Decisions On Project Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We define public acceptability of renewable energy projects as the extent to which people evaluate those projects (un)favourably (from now on referred to as "project acceptability"). Indeed, renewable energy projects may be delayed or cancelled if there is strong public resistance (Boyd, 2017;Papazu, 2017;Shaw et al, 2015). Hence, an important question is which factors and processes affect project acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…One key challenge is public acceptability of renewable energy projects, namely the extent to which the public evaluates a renewable energy project favourably or unfavourably. Many renewable energy projects face public resistance, which can seriously inhibit the implementation of those projects (Devine-Wright, 2007, 2009Guo et al, 2015;Papazu, 2017). This study aims to further our understanding of what influences public acceptability of renewable energy projects.…”
Section: Introductionmentioning
confidence: 99%